Research advances in the etiology of in-stent restenosis of coronary arteries - Bai, Hangrui; Zhang, Bin; Sun, Yurong; Wang, Xinran; Luan, Bo; Zhang, Xiaojiao (Frontiers in Cardiovascular Medicine, 2025)
This article conducts a systematic literature analysis, focusing on exploring the etiological factors of coronary in—stent restenosis(ISR). It is found that the occurrence of ISR is influenced by a variety of factors, including patient—related biological factors (such as diabetes and smoking), lesion anatomical factors (such as calcification and lesion length), and factors related to the surgical procedure (such as incomplete stent expansion and stent malposition). Regarding the prevention of coronary in—stent restenosis, individualized treatment strategies need to be developed by combining patient characteristics, lesion anatomy, and surgical techniques.